EVALUATION OF PHYTOCONSTITUENTS, AND ANTIMICROBIAL AND ANTIOXIDANT ACTIVITY OF JUGLANS REGIA FROM KASHMIR REGION - KHAN, ISHFAQ; CHAUHAN, NEHA; PK, CHAUHAN; KHAN, MOHD. AZHAR (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objectives: The main focus of the present study was to evaluate the antimicrobial efficacy (against oral pathogenic bacteria), free radical scavenging activity, and total phenolic and flavonoids content (TPC and TFC) of methanolic extract (ME) of J. regia obtained from Kashmir region. Methods: The plant part was collected and its ME was prepared. ME was subjected to antibacterial activity against oral bacteria such as Staphylococcus aureus, Streptococcus mutans, and Pseudomonas aeruginosa. The free radical scavenging activity was determined using 2,2-diphenyl- 1-picrylhydrazylhydrate (DPPH) assay. TPC and TFC were also determined using a standard curve equation of gallic acid and quercetin. A standard curve using different concentrations of gallic acid and quercetin was drawn from which the concentration of phenols in the test sample was calculated and expressed in mg/g. Results: The ME of J. regia was found effective against all the strains of microorganisms responsible for oral infection understudy. It was also observed that scavenging of DPPH increased with the increase in concentration for both standard ascorbic and methanolic bark extract of J. regia showing its antioxidant potential. The TPC and TFC of ME was found to be 43.35±0.079 and 17.28±0.125. Conclusions: The results obtained from the study clearly indicate that the walnut bark from Kashmir region can be a good candidate for employment as an antibacterial against oral pathogens. J. regia bark was found to be a good source of healthy compounds such as phenolic and flavonoids, suggesting that its bark could be useful to prevent diseases in which free radicals are present.